“Around the clock”: Exploring health care professionals’ experience of discharge of older people during out of hours from the emergency department: A qualitative study - Mary Dunnion; Debbie Goode; Assumpta Ryan; Sonja McIlfatrick (PLoS ONE, 2025)
Background Older adults constitute a considerable number of attendances at emergency departments (EDs). Whilst many require hospital admission, a greater focus now is on admission avoidance with older adults being subsequently discharged from EDs. Little is known, however, about the experiences out of hours (OOH) when specialist older person support services are unavailable. Aim To explore senior health care professionals’ experiences of discharging older people during out of hours from EDs. Method A qualitative study involving individual semi-structured interviews was used to explore the experiences of healthcare professionals. Fourteen participants in total responded from a wide geographical spread. Data analysis was undertaken using Braun and Clarke’s (2022) six-step framework for Thematic Analysis. Results One overarching theme was identified focusing on risks and safety for the older person whilst being discharged OOH from the ED. Three sub-themes included “Should they stay, or should they go?”, “Bright lights and noise”, and “New ways of working”, which included risks in discharging an older person OOH from the ED, risks in delaying discharge, and recommendations for future practice. Significant differences were reported between office hours and OOH discharge of older adults from the ED. Diversity in practice assessments, and resources available was also evident across EDs. Significant adverse consequences were identified for older adults having to stay for prolonged periods in the ED. Conclusions There have been many welcome developments in healthcare services for older people who attend and are subsequently discharged from the ED. However, further innovative practice and collaboration with senior decision makers is needed to meet the healthcare needs of a rapidly ageing population. Safe, equitable and effective discharge practice 24/7 should be a norm for all older people in every ED regardless of location. Gaps in care identified must be addressed taking cognisance of the relevant recommendations for future practice.